2021
DOI: 10.3389/fonc.2021.696532
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1-AKT Positive Regulation Loop Provides Venetoclax Resistance in AML

Abstract: Forkhead box protein M1 (FOXM1) is a crucial regulator of cancer development and chemoresistance. It is often overexpressed in acute myeloid leukemia (AML) and is associated with poor survival and reduced efficacy of cytarabine therapy. Molecular mechanisms underlying high FOXM1 expression levels in malignant cells are still unclear. Here we demonstrate that AKT and FOXM1 constitute a positive autoregulatory loop in AML cells that sustains high activity of both pro-oncogenic regulators. Inactivation of either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
(53 reference statements)
2
21
0
Order By: Relevance
“…Also in this case, analysis of FOXM1 in Hep3B cells revealed a reduction of phosphorylation and amount of FOXM1 protein in samples treated with palbociclib, both as a single agent and in combination with miR-199a-3p ( Figure 2 C). As FOXM1 activation is also AKT-dependent, 29 , 30 inhibition of FOXM1 was also mediated by miR-199a-3p, as we previously reported 15 ( Figure 2 C).
Figure 2 miR-199a-3p increased palbociclib efficacy on human HCC cells in vitro and in vivo (A) Hep3B cells were transduced with an Adeno Associated Virus expressing miR-199a-3p (AAVV-199) or with a control AAVV (AAVV-CTRL) at MOI = 100.
…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Also in this case, analysis of FOXM1 in Hep3B cells revealed a reduction of phosphorylation and amount of FOXM1 protein in samples treated with palbociclib, both as a single agent and in combination with miR-199a-3p ( Figure 2 C). As FOXM1 activation is also AKT-dependent, 29 , 30 inhibition of FOXM1 was also mediated by miR-199a-3p, as we previously reported 15 ( Figure 2 C).
Figure 2 miR-199a-3p increased palbociclib efficacy on human HCC cells in vitro and in vivo (A) Hep3B cells were transduced with an Adeno Associated Virus expressing miR-199a-3p (AAVV-199) or with a control AAVV (AAVV-CTRL) at MOI = 100.
…”
Section: Resultssupporting
confidence: 82%
“…In fact, its lack of phosphorylation by CDK4/6 promotes its degradation and inhibition of its activity. Furthermore, inhibition of FOXM1, which is also activated via the AKT pathway, 29 , 30 can be at the same time sustained by miR-199a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CD44 is a potential therapeutic target to resensitize AML cells to venetoclax. Inactivation of FOXM1, an important protein in cancer development and chemoresistance [ 64 ], as part of a FOXM1-AKT-positive regulation circuit, effectively sensitizes venetoclax-resistant AML cells [ 147 ], also making FOXM1 an interesting therapeutic target to combine with targeting BCL-2.…”
Section: Prediction Of Active Venetoclax-based Combination Therapies ...mentioning
confidence: 99%
“…It was found that GLI1 can promote AML cell proliferation directly through PI3K signaling pathway and can be reversed by AKT inhibitors ( 66 ). AKT can enhance FOXM1 expression and form a positive feedback to enhance venetoclax resistance in FLT3 wild-type AML ( 67 ). Therefore, FOXM1 inhibitors may be a promising therapeutic strategy due to their dual signaling pathway regulations.…”
Section: Dormancy Of Lscs and Drug Resistancementioning
confidence: 99%